DISTRIBUSI KELAS UKURAN KERANG SIMPING PINGGIR (Placuna Placenta, Linn, 1758 :Pelecypoda) DI PERAIRAN GENUK SEMARANG - Isti Anti, Diah Ayu; Suryono, Chrisna Adhi; Irwani, Irwani (977-2407769)
Placuna placenta are often called scallop shells included in the phylum mollusca, Pelecypoda Class, and Family Placunidae. The research was held on October until December 2012. The research was conducted at the research 8 stations. The materials have been used are scallop shells, sea water, and the substrate of water base. The method used in this research is descriptive method and purposive sampling method as the method in determining the location of doing research with interval of 1 month. The result of this research is that the distribution of scallop shells in Genuk waters found in October was 63 ind / ha, in November 582 Ind / ha and in December 155 ind/ha. The Results of the linear regression about relationship length and weight of the Scallop shells in the period October- December included on negative allometric because the regression coefficient (b) less than 3. The abundance of scallop shells on research site influenced waters condition quality and the organic materials in sediment.